Assessment of the changes in alveolar bone quality after fixed orthodontic therapy: A trabecular structure analysis - Abdolaziz Haghnegahdar; Hooman Zarif Najafi; Maryam Sabet; Maryam Saki (Tabriz University of Medical Sciences, 2016)
Background. Tooth displacement changes the periodontium. The aim of orthodontic treatment is desired tooth movement with minimum side effects on the alveolar bone quality. The aim of the present study was to assess changes of alveolar trabeculation in children, young adults and adults and the two genders. Methods. In this cross-sectional study, 63 patients who had been treated in Department of Orthodontics, School of Dentistry, Shiraz University of Medical Sciences, Shiraz, Iran, were chosen with convenient sampling method. They were divided into three groups based on their age. Their digitized panoramic radiographs (PRs) were evaluated at six interdental sites from the mesial aspect of the mandibular second molars to the distal aspect of the mandibular first premolars using a visual index. The trabeculation pattern was assigned as either dense (score 3), dense-sparse (score 2) or sparse (score 1). Data were imported to SPSS. Mean of the scores before treatment (score B) and mean of them after treatment (score A) were compared for each group with paired t-test. Changes between score B and sore A of the groups were compared using one-way ANOVA and post hoc tests. Results. Mean score A was significantly higher than mean score B in children (P = 0.001). In contrast, mean score A was significantly lower than mean score B in young adults (P = 0.003). Conclusion. Orthodontists should be cautious when treating young adults and adults regarding the probable, yet possibly temporary, negative effects of orthodontic therapy on the alveolar bone quality.